On legal and factual grounds of relevance of confessional cemeteries and religious sites of common cemeteries to real estate property objects for religious purposes (Stato, Chiese e pluralismo confessionale, 2017)
Article peer reviewedSUMMARY: 1. Introduction: formulation of the Problem – 2. The genesis of the legal status of religious cemeteries – 3. The meaning of confessional cemeteries and religious sites of common cemeteries, attached in different religions – 4. The nature of confessional cemeteries from the perspective of the right – 5. The issue of confessional graves in the Russian Federation legislation – 6. The theme of religious burials in the judicial practice of the courts of the Russian Federation – 7. Conclusions.ABSTRAC: The article is devoted to problems arising in implementation of the provisions of Federal Law from 30.11.2010 № 327-FZ (as amended on 23.06.2014) «On the transfer of property for religious purposes under state or municipal property to religious organizations». The article studies legal and factual grounds of relevance of confessional cemeteries and religious sites of common cemeteries to the category of real estate property objects for religious purposes.Keywords: civil law, real estate property for religious purposes, religious organization, ownership, real property, gratuitous transfer of property.
Keywords: Varie